Applying the Viable System Model to an Organization with CSR Goals: The Case of a Charity Organization (European Journal of Marketing and Economics, 2026)
Designing and adapting organizations to secure viability and increase performance is a challenge. Research models often fail to integrate corporate social responsibility (CSR) aspects in the concept development and its implementation. Therefore, the aim of this study is to propose a holistic approach how organizations can be designed, changed and managed considering its implications to service management under a CSR approach. Hereby the Viable System Model was applied. Its structure can be applied to any kind of structured organization and for its management with goals to be achieved in modern society; however focus of the research is the cluster of charity organizations. Goal of the developed model is to be able to react to all potential organizational environments by taking decisions correctly and in the right moment based on the needed information reducing service lead times and manpower allocation as well as increasing the service level. To ensure this, service management tasks were assigned and standardized communication channels were defined. In conclusion this proposed approach empowers organizations to have internal mechanisms to secure viability by pursuing the goal of a high performance CSR approach.
Keywords: Cybernetics, Viable System Model, Service management, Organizational Model, Corporate Social Responsibility, Charity Organization